Islam sebagai Agama yang Mengutamakan Pendidikan: Studi Penelitian Hadis Tentang Pentingnya Pendidikan - Ulya, Zihniatul (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2024)
Education is a field for seeking provisions to make a life, because to make a life, humanity needs education that will teach procedures so that relationships with the creator, government, each other and the environment can run well. Therefore, education is very important so that state law and religion, especially Islam, requires its followers to seek knowledge or pursue education, as is contained in the hadiths of the Prophet Muhammad SAW which discuss the importance of education. The Prophet Muhammad SAW himself had practiced this education with his friends, so that it was followed by his friends and so on in all scientific disciplines, especially in spreading and teaching Islamic teachings. Until now, we have found that in Indonesia itself there are many educational institutions spread throughout Indonesia, both formal and non-formal. The aim of this research is to explore motivation for learning through descriptions of several hadiths of the Prophet who commanded the pursuit of knowledge. The data collection process was carried out by collecting in-depth information and data through various literature, notes, hadith books, magazines, books, journals, articles and various other sources. Then, that is what is studied, analyzed and described. The results of the analysis gave rise to three discussions, namely the meaning of Hadith and education, the priority of knowledgeable people, and Hadith about the importance of education. A study of  these three themes is very useful for understanding how important education is from a Hadith perspective.